Inventory of Types of Anura Order in Kedung Klewer Waterfall - Pramudita, Novia Linggar; Khanafi, Wahibah; Ludhfiyah, Anggun; Indra, Ismu Nadhira; Fauzi, Ria Rizki; Wibisana, Oki Rahmatirta (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2024)
Kedung Klewer Waterfall located in Kediri, East Java, is a famous natural tourist attraction. However, research on the inventory of the Anura order there is still very limited. This study aims to identify and describe the species of the Anura order in the Kedung Klewer Waterfall Tourism Area and contribute to the preservation of the Anura order in the region. This research was conducted on January 6-8, 2022 using the Visual Encounter Survey (VES) method combined with transect lines. Based on the results of research and discussion, it can be concluded that the Anura order found 17 individuals in the Kedung Klewer Kediri waterfall area consisting of 4 families, for the Ranidae Family 2 species were found, namely Wijayarana masonii and Odorana hosii, the Dicroglossidae family found 1 species, namely Limnonectes microdiscus, the Megophrylidae family found 1 species, namely Leptobrachium hasseltii, and Family Bufonidae found 1 species, Phrynoidis asper.